Efektifitas Baby Massage Terhadap Kenaikan Berat Badan Dan Kualitas Tidur Bayi Di Asyfalesha Mom n’ Baby Care - Hartati S; Asrida A; Siswati Rahmadyana (Journal Innovation In Education, 2023)
Infancy is a golden period for a child's growth and development so it needs special attention. One of the factors that influences a baby's growth and development is sleep and rest. The need for sleep is not only seen from the quantity aspect but also the quality. With good quality sleep, the baby's growth and development can be achieved optimally. One way that can be used to fulfill these needs is baby massage. Baby massage is a gentle stroking or massaging therapy for babies, this is stimulation through tactile stimulation, gentle massage approaching soft and gentle massage on the surface of the baby's skin gently, on the tissues and organs of the body. Baby massage is useful for increasing the baby's concentration and making the baby sleep soundly, to increase the baby's growth and weight, increase the body's endurance, build bonds of love between parents and children and improve blood circulation and breathing. A baby's weight is influenced by heredity, nutrition, environment, gender and social status. Body weight is an anthropometric indicator for assessing growth in babies or children. Balanced nutrition and basic health care in the form of immunizations. Regular massage for babies can increase the baby's weight and the length of time the baby sleeps. This happens when the baby is massaged and the baby feels relaxed so it is easy for the baby to sleep. The initial survey was conducted through direct interviews with AsyfAlesha Mom n' Baby Care, which opened a baby massage practice. Therefore, researchers are interested in examining the effectiveness of baby massage on weight gain and baby sleep quality at AsyfAlesha Mom n' Baby Care, whether its implementation is effective in supporting weight gain and baby sleep quality to prevent stunting in babies.